(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines some aspects of the development of mountain and pre-mountain ecotourism in Dehkhanabad district, especially the natural and territorial conditions, and how pre-mountain ecotourism is directly related to the interaction between nature and man. There are many natural attractions in the Kashkadarya Basin, which directly serves as a place for tourists to relax and recuperate. In this regard, it was informed that the mountains and mountainous areas in the mountainous region are a reserve that is not open to local and foreign tourists and some aspects of ecotourism.